2022
DOI: 10.1097/01.jaa.0000832596.64788.f1
|View full text |Cite
|
Sign up to set email alerts
|

PAs and NPs improve patient care and productivity in a radiology consult practice

Abstract: Services and Operations, for the illustrations accompanying this article.JAAPA and JAANP have arranged to publish this article simultaneously in their July 2022 issues. Although the two articles may have minor style differences, they are essentially the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…A recent example of this is research by Virarkar and colleagues that reported on a new care model designed to improve a radiology practice by integrating PAs and NPs into an abdominal radiology consult service. 8 Additionally, as scope-of-practice laws are liberalized, PA productivity likely will be affected. A 2017 study by Timmons demonstrated that reducing practice barriers for PAs and NPs-specifi cally allowing them to prescribe controlled substances-was associated with substantial cost savings to Medicaid patients.…”
Section: Assessing Pa Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example of this is research by Virarkar and colleagues that reported on a new care model designed to improve a radiology practice by integrating PAs and NPs into an abdominal radiology consult service. 8 Additionally, as scope-of-practice laws are liberalized, PA productivity likely will be affected. A 2017 study by Timmons demonstrated that reducing practice barriers for PAs and NPs-specifi cally allowing them to prescribe controlled substances-was associated with substantial cost savings to Medicaid patients.…”
Section: Assessing Pa Productivitymentioning
confidence: 99%
“…Research in the last decade has begun to investigate clinician productivity in specific specialties and settings, including novel ways to structure team practice to increase delivery quality and increase productivity. A recent example of this is research by Virarkar and colleagues that reported on a new care model designed to improve a radiology practice by integrating PAs and NPs into an abdominal radiology consult service 8…”
mentioning
confidence: 99%
“…One study found increased physician Relative Value Units (RVUs) and overall revenue after the integration of PAs and NPs into a radiology practice. 18 Another study involving nearly 28 000 family physicians found that including PAs or NPs was associated with significantly larger patient panel sizes and a greater number of patient care activities. 6 However, these studies are limited by reporting practice-level outcomes associated with PA and NP employment and focusing on a single practice site or physician specialty.…”
Section: Introductionmentioning
confidence: 99%